2014
DOI: 10.1021/ol5008586
|View full text |Cite
|
Sign up to set email alerts
|

Toward Perylene Dyes by the Hundsdiecker Reaction

Abstract: An efficient method to synthesize 3,4,9,10-tetrabromoperylenes is reported under optimized Hunsdiecker conditions. Various octasubstituted perylenes were obtained by reaction of 1,6,7,12-tetrachloro-3,4,9,10-tetrabromoperylene with phenol, trimethylsilyl chloride, cooper cyanide, or sulfur via metal-catalyzed couplings or nucleophilic substitutions. These new perylenes show completely different optical and redox properties, thus opening a facile way to develop new chromophophore structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 24 publications
3
64
0
Order By: Relevance
“…Rylenes can also be regarded as a narrow GNR, and this relation could be further corroborated by a chemical reaction, the Hundsdiecker decarboxylation. 64 Thereby, PDIs were transformed into tetrabromo perylenes 16 (Scheme 7). These compounds were used by Lifeng Chi and Harald Fuchs as unique building blocks for GNR 16a formation on gold surfaces.…”
Section: Scheme 5: Synthesis Of Graphene Nanoribbons In Solutionmentioning
confidence: 99%
“…Rylenes can also be regarded as a narrow GNR, and this relation could be further corroborated by a chemical reaction, the Hundsdiecker decarboxylation. 64 Thereby, PDIs were transformed into tetrabromo perylenes 16 (Scheme 7). These compounds were used by Lifeng Chi and Harald Fuchs as unique building blocks for GNR 16a formation on gold surfaces.…”
Section: Scheme 5: Synthesis Of Graphene Nanoribbons In Solutionmentioning
confidence: 99%
“…The absorption spectrum of 5‐OMe is slightly blue‐shifted compared to that of 5 , and shows an even larger split width of the Q‐like bands (6029 cm −1 ; Figure ). Such significant bathochromic shifts in the absorption spectra of 5 and 5‐OMe are also observed in those of disulfide‐appended polyaromatic hydrocarbons . These perturbations in the absorption spectrum of 5 are completely lost in the absorption spectrum of S,S ‐dioxodithiazolosubporphyrin 8 that shows almost the same spectral features as those of 1 .…”
Section: Resultsmentioning
confidence: 97%
“…In order to calculate the absolute energies of LUMO level with respect to the vacuum level, the redox data are standardized to the ferrocene/ferricenium couple which has a calculated absolute energy of -4.8 eV 32 . The data related to LUMO level energies of dyes are presented in Table 3.…”
Section: Lowest Unoccupied Molecular Orbital (Lumo)mentioning
confidence: 99%
“…Highest occupied molecular orbital (HOMO) Table 4 depicts the highest occupied molecular orbital energy levels, which are calculated using the standard reported procedure [32]. Considering the energy range from -6.64 to -7.54 eV for xanthene dyes 3a-e and 6a-e, it is observed that for dyes 3a and 6a HOMO energy levels are at very low energy carboxylic groups present in the xanthene chromophore while 6b and 6e have high HOMO energy levels due to the mesomorphic and the inductive effect of hydroxyl groups present in dye molecule.…”
Section: Band Gap Energy (Eg)mentioning
confidence: 99%